MRI-Detected Brain Lesions and Cognitive Function in Patients With Atrial Fibrillation Undergoing Left Atrial Catheter Ablation in the Randomized AXAFA-AFNET 5 Trial - Hausler, Karl Georg; Eichner, Felizitas A.; Heuschmann, Peter U.; Fiebach, Jochen B.; Engelhorn, Tobias; Blank, Benjamin; Callans, David; Elvan, Arif; Grimaldi, Massimo; Hansen, Jim; Hindricks, Gerhard; Al-Khalidi, Hussein R.; et al. (Circulation, 2022)
BACKGROUND: We aimed to assess the prevalence of ischemic brain lesions detected by magnetic resonance imaging and their association with cognitive function 3 months after first-time ablation using continuous oral anticoagulation in patients with paroxysmal atrial fibrillation (AF).
CRIS-Team WoS Importer:2022-04-01